2014
DOI: 10.1017/s0305000913000603
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in phonological development: the case of word-final cluster acquisition in Welsh–English bilingual children

Abstract: This study provides the first systematic account of word-final cluster acquisition in bilingual children. To this end, 40 Welsh-English bilingual children differing in language dominance and age (2;6 to 5;0) participated in a picture-naming task in English and Welsh. The results revealed significant age and dominance effects on cluster acquisition, with greater overall accuracy on the English clusters. Interestingly, although the Welsh-dominant children outperformed the English-dominant ones on the Welsh clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
4
19
0
Order By: Relevance
“…In fact, her results showed that speech production proficiency in one language was the best predictor of segmental accuracy in the other language. Other studies of bilingual children learning other language pairs have documented correlations and interaction between phonological systems (Mayr et al, 2015;Kehoe, 2015). Taken together, these findings suggest, in line with the predictions of the Unified Competition Model (MacWhinney, 2005), that speech production abilities in one language may be highly predictive of speech production abilities in the other language, at least when the languages share similar sounds and phonological structures.…”
Section: Relationships Between Phonological Skillssupporting
confidence: 77%
See 2 more Smart Citations
“…In fact, her results showed that speech production proficiency in one language was the best predictor of segmental accuracy in the other language. Other studies of bilingual children learning other language pairs have documented correlations and interaction between phonological systems (Mayr et al, 2015;Kehoe, 2015). Taken together, these findings suggest, in line with the predictions of the Unified Competition Model (MacWhinney, 2005), that speech production abilities in one language may be highly predictive of speech production abilities in the other language, at least when the languages share similar sounds and phonological structures.…”
Section: Relationships Between Phonological Skillssupporting
confidence: 77%
“…Goldstein et al, 2010). For instance, as predicted by the Unified Competition Model (MacWhinney, 2005), negative transfer should be particularly seen at early stages of bilingual development and when one language is dominant over the other, since children would particularly rely on phonological structures from their stronger languagebased on more frequent and possibly more salient cuesfor productions in their non-dominant language (Munro, Ball, Müller, Duckworth & Lyddy, 2005;Mayr, Howells & Lewis, 2015). However, transfer from the dominant language should decrease as exposure to and practice with the non-dominant language increases, making cues specific to this language gain strength and exert more influence on the development of its phonological system.…”
Section: Relationships Between Phonological Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the study hence did not find any effect of linguistic experience. This is surprising considering most previous studies on bilingual speech have found differences between monolinguals and bilinguals (e.g., Kehoe et al, 2004;Fowler et al, 2008;Guion, 2003;Paradis, 2001;but see MacLeod, Stoel-Gammon & Wassink, 2009;Mennen, 2004), and between bilinguals who differ in their linguistic experience (e.g., Mayr, Howells & Lewis, 2015;Simonet, 2010).…”
Section: Linguistic Experience Peer Group Identity and Welshnessmentioning
confidence: 87%
“…The language that the child hears and uses the most frequently is typically his dominant language. Many studies show that the dominant language of a bilingual is associated with faster phonological acquisition (Ball, Müller, & Munro, 2001;Law & So, 2006;Mayr, Howells, & Lewis, 2015). Other studies have not found dominance to be useful in accounting for results (Rose & Champdoizeau, 2007).…”
Section: Factors Accounting For Phonological Performance In Monolingumentioning
confidence: 99%